Verbal Representation of the Concept “Sermon” (Based on the Association Test) - Chmil, Natalia (East European Journal of Psycholinguistics, 2017)
The investigation of religious discourse is widespread in Ukraine now because of great confidence in the сhurch. The aim of this research is to analyze verbal representation of the concept “sermon”. Free word association test (WAT) has been used for psycholinguistic analysis. The aim of this research is to analyze the verbal representation of the concept “sermon”. Free word association test (WAT) has been used for psycholinguistic analysis. The definitions of concept and religious concept as a multidimensional mystical semiotic formation are highlighted. The paper overviews the main linguistic researches of sermon by Ukrainian and foreign scholars. Certain communicative features of religious sermons have been described. As a result of the free WAT, 260 responses to the stimulus word “sermon” were, among them 97 different associations. Among the most frequent responses were “priest”, “story”, “edification” and “attitude”. The logical and grammar characteristics of the obtained associations have been analyzed. It has been shown that central paradigmatic reactions to the stimulus word “sermon” predominate. The thematic features of the associations to “sermon” have been analyzed. Four different thematic groups have been identified: situation of sermon, genre features, people (sermon participants), emotions and evaluation. The most numerous thematic group is “genre features”. The least numerous thematic group is “sermon participants”. Prospects for further study of this problem lie in an in-depth psycholinguistic analysis of religious discourse. References Anikushyna, M. V. (2008). O kompozitsii teksta sovremennoy hristianskoy angloyazyichnoy propovedi [On text composition of the modern Christian English-language sermon]. Proceedings of Tula State University. Humanitarian Sciences, 2, 191–196. Bizjak Končar, A. (2008). Contemporary sermons: From grammatical annotation to rhetorical design. Systemic Functional Linguistics in Use. Odense Working Papers in Language and Communication, 29, 503–521. Esimaje, U. A. (2014). A descriptive survey of the character of English lexis in sermons. SAGE Open, 4(4), 1–16. Goroshko, Ye. I. (2001). Integrativnaya Model Svobodnogo Assotsiativnogo Eksperimenta [Integrative Model of Free Associative Test]. Kharkiv: RA–Karavella. Zalevskaya, A. A. (2001). Psiholingvisticheskiy podhod k probleme koncepta [Psycholinguistic Approach to the Concept]. In: Methodological Problems of Psycholinguistics, (pp. 36–45). Voronezh: VGU. Zasiekina, L. V. Zasiekin, S. V. (2008) Psykholinhvistychna Diahnostyka [Psycholinguistic Diagnostics]. Lutsk : Vezha. Zlenko, S. (2017). The trust to social institutions. Retrieved from http://www.kiis.com.ua/?lang=ukr&cat=reports&id=678&page=1. Istomina, I. A. (2012). O dialogichnosti tekstov sovremennoy pravoslavnoy propovedi [Dialogic texts of modern Orthodox sermon]. Scientific Proceedings of Kazan University. Humanitarian Sciences, 154(5), 156–163. Martinek, S. V. (2011). Empirychni y eksperymentalni metody u suchasnii kohnityvnii linhvistytsi [Empirical and experimental methods in current cognitive linguistics]. Bulletin of Lviv University. Philological Series, 52, 25–32. Muntyan, L. V. (2013). Kontseptual’nyy analiz ta metody doslidzhennya verbalizovanykh kontseptiv [Conceptual analysis and methods of research verbalized concepts]. Scientific Notes. Philological Series, 33, 103–105. Postovalova, V. I. (2012). Religioznyie kontsepti v teolingvisticheskom predstavlenii [Religious concepts in teolinguistic representation]. Teolinguistika. International Thematic Collection of Papers. Beograd: Belgrade University, 143–152. Prokhvatilova, O. A. (1999). Pravoslavnaya propoved’ i molitva kak fenomen sovremennoy zvuchashchey rechi [Orthodox sermon and prayer as a phenomenon of modern sounding speech]. Volgograd: Volgograd State University. Rozhylo, M. A. (2014). Komunikatyvnyi potentsial relihiinoho internet-tekstu (na prykladi propovidei Mytropolyta Lutskoho i Volynskoho Mykhaila) [Communicative Potential of Religious Internet text (based on sermons by Metropolitan Bishop of Lutsk and Volyn Mykhail)]. Media, Globalization, Social Mimicry: Scientific Online Symposium. (101-106). Lutsk, Ukraine: Lesya Ukrainka Eastern European National University. Sergeyeva, Ye. V. (2007). Leksicheskaya eksplikatsiya kontsepta “religiya” v russkom yazyke [Lexical explication of the concept “religion” in Russian]. Political Linguistics, 2(22), 151–165. Stebel’kova, N. A. (2012). Lingvisticheskie osobennosti anglojazychnoj propovedi kak zhanrovoj raznovidnosti teologicheskogo diskursa [Linguistic features of the English speaking sermon as a genre variety of theological discourse]. Bulletin of Moscow State Linguistic University, 6(639), 205–212. 16. Yasinovskaya, Ye. G. (2011). O spetsifike religioznogo diskursa [On the specifics of religious discourse]. Bulletin of Moscow State Linguistic University, 10(616), 179–186.